Exploring Paranoid Schizophrenia: A Clinical Case Study in Surabaya - Imtiyaaz Nahdiyant Ekaputri; Qurrota A'yuni Fitriana Qurrota (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2024)
This study aims to identify symptoms, causes and diagnosis of paranoid schizophrenia of patient in one of hospital at Surabaya. The research method used is a qualitative method with a case study technique. To explore in depth an event in a real context through observation, interviews, and documentation. The patient is a 32-year-old man who believes he is a person with magical powers. He has delusions and auditory hallucinations such as supernatural whispers. He experienced a divorce with his wife and have conflict with his siblings. The results of the data show that the emergence of paranoid schizophrenia is caused by stress experienced by patient and he cannot solve his problems. The cause of schizophrenia is also experienced due to genetic factors, brain biochemical factors, or organic disorders in the brain. This shows that paranoid schizophrenia occurs due to internal and external factors.